2021
DOI: 10.1039/d1dt01251g
|View full text |Cite
|
Sign up to set email alerts
|

Layered terbium hydroxides for simultaneous drug delivery and imaging

Abstract: Layered rare-earth hydroxides have begun to gather increasing attention as potential theranostic platforms owing to their extensive intercalation chemistry combined with magnetic and fluorescent properties. In this work, the potential...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 93 publications
1
8
0
Order By: Relevance
“…For initial synthesis optimisation experiments, the temperature was set to 100 °C and 200 °C (50 °C above and below the previously reported method), 1 with incubation times of 10 and 24 h (compared to 15 h originally). The fill volumes chosen were approximately half the capacity of the reactor (10 ml) and full capacity (18 ml), whilst leaving some room for air in order to prevent vessel leakage.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For initial synthesis optimisation experiments, the temperature was set to 100 °C and 200 °C (50 °C above and below the previously reported method), 1 with incubation times of 10 and 24 h (compared to 15 h originally). The fill volumes chosen were approximately half the capacity of the reactor (10 ml) and full capacity (18 ml), whilst leaving some room for air in order to prevent vessel leakage.…”
Section: Resultsmentioning
confidence: 99%
“…These guest moieties may be selected to exert a therapeutic effect, as well as to modify the overall contrast properties of the parent LRH material. Moreover, LRH materials have previously been shown to be stable at physiological pH 1 and well-tolerated in cytotoxicity studies 7,8 (though in vivo applications of LRHs are thus far extremely limited in scope, and long-term toxicity is not yet explored). As such, LRHs are attracting increasing interest in the field of theranostics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with the drug delivery research reported in the previous literature, this system has more unique nanostructures, richer luminescent, and magnetic functions. [12,13,52] Moreover, since other similar LDH has been proved to deliver a variety of drugs, proteins, etc. and produce corresponding performance changes, [52][53][54] the preparation of YTG-ASA integrated with multiple functions in one drug delivery system is expected to be gradually extended to other drugs in the future, which has wide prospects in biomedical fields.…”
Section: Discussionmentioning
confidence: 99%
“…[ 12,13,52 ] Moreover, since other similar LDH has been proved to deliver a variety of drugs, proteins, etc. and produce corresponding performance changes, [ 52–54 ] the preparation of YTG‐ASA integrated with multiple functions in one drug delivery system is expected to be gradually extended to other drugs in the future, which has wide prospects in biomedical fields.…”
Section: Discussionmentioning
confidence: 99%